2015
DOI: 10.1021/acs.jpclett.5b01252
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Binding Energy and the Nature of Emissive States in Organometal Halide Perovskites

Abstract: Characteristics of nanoscale materials are often different from the corresponding bulk properties providing new, sometimes unexpected, opportunities for applications. Here we investigate the properties of 8 nm colloidal nanoparticles of MAPbBr3 perovskites and contrast them to the ones of large microcrystallites representing a bulk. X-ray spectroscopies provide an exciton binding energy of 0.32 ± 0.10 eV in the nanoparticles. This is 5 times higher than the value of bulk crystals (0.084 ± 0.010 eV), and readil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
254
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(274 citation statements)
references
References 45 publications
19
254
1
Order By: Relevance
“…S11), indicating good color purity. The samples show a Stokes shift of~39 meV between the absorption band edge and the emission line, implying a direct exciton recombination process [38]. A power law dependence (I∝L k ) was observed with k values near 1.3 (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…S11), indicating good color purity. The samples show a Stokes shift of~39 meV between the absorption band edge and the emission line, implying a direct exciton recombination process [38]. A power law dependence (I∝L k ) was observed with k values near 1.3 (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…However, single-particle measurements are sometimes necessary, in order to obtain accurate correlations between their optical properties and size/morphology. 27,71,[94][95][96][97][98][99] Tian et al 100 provided direct visualization of the photogenerated carrier diffusion in single MAPbBr 3 and MAPbI 3 NWs and nanoplates using time-resolved PL-scanning microscopy (Figures 8a-e). This technique is based on the photoexcitation of a single particle at one specific position and subsequently scanning the substrate at different positions by time-resolved PL as a function of delay time.…”
Section: Quantum Confinement In Perovskite Ncsmentioning
confidence: 99%
“…We then explain how EAS can help nanoplatelets of various thicknesses. [43][44][45][46][47] The latter are denominated 'quasi-2D' (q-2D), as they exhibit a quasi-two-dimensional structure comprising several (3-5) layers of perovskite unit cells, stabilized by a capping layer of octylammonium cations. Each of these nanostructures exhibits a unique optical signature, observable from their absorbance spectrum as shown in Fig.…”
Section: Eas Of Molecules or Confined Excitonic Statesmentioning
confidence: 99%
“…This EA response has been previously assigned to a quadratic Stark effect, thus arising from the presence of confined excitons. [43] However, such an assignment is questionable, notably due to the detailed work by Ziffer et al, in which EAS of thinfilm of methylammonium lead-iodide perovskite was carried out. [36] In this context, it was shown that the obtained EA response at room temperature was better described by the low-field FKA model.…”
Section: Unravelling the Properties Of Photocarriers Using Eas: An Exmentioning
confidence: 99%